The t-unique coding domain is important to the transformation maintenance function of the simian virus 40 small t antigen. - Bikel, I (1986)
The small t antigen (t) of simian virus 40, a 174-amino-acid-containing protein, when present together with the other early viral protein, large T antigen (T), plays an important role in the maintenance of simian virus 40-induced neoplastic phenotype in certain cells. Indeed, each protein functions in a complementary manner in this process. The t coding unit is composed of two segments, a 5' region of 246 nucleotides which is identical to that of the corresponding 5' region of the T coding unit and a 3' segment of 276 nucleotides which is unique. Two mutant, t-encoding genomes, one bearing a missense and the other a nonsense mutation at the same point in the t-unique coding region were constructed in vitro and found to be defective in their ability to dissolve the actin cytoskeleton of rat fibroblasts and to complement T in the growth of mouse fibroblasts in soft agar. Therefore, the unique segment of the t gene encodes a portion of the t molecule which is essential to its transformation maintenance function.